Strategi Pemberdayaan Ekonomi Protektif Di Pondok Modern Darussalam Gontor Putri Kampus 8 Lampung: Protective Economic Empowerment Strategy at Darussalam Gontor Putri Modern Islamic Boarding School, Campus 8, Lampung - Zaim, Zaimatu Aisyaturrohma; Abizar; Ulil Albab (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2025)
This study aims to provide an in-depth analysis of the protective economic empowerment strategy implemented at Pondok Modern Darussalam Gontor Putri Campus 8. The concept of protective economic empowerment does not merely focus on improving the economic welfare of female students (santriwati), teachers, and the surrounding community, but also functions as a safeguard to preserve the religious values and cultural traditions that are deeply rooted in the pesantren environment. Using a descriptive qualitative approach, this research gathers information through observation, interviews, and documentation of various ongoing economic programs. The main areas of focus include the development of pesantren cooperatives, the establishment of diverse micro-enterprise units, and the implementation of entrepreneurship training programs based on Islamic principles that aim to foster Islamic entrepreneurial character among students. The strategies are designed to encourage economic independence without compromising the religiosity that forms the core identity of the pesantren. The findings reveal that the implementation of protective economic empowerment strategies has significantly enhanced the pesantren’s capacity to build a sustainable and independent economic ecosystem. All economic activities are managed in accordance with sharia principles, such as interest-free financial management, the application of Islamic business ethics, transparency, and fairness in transactions. This approach not only strengthens the pesantren’s economic self-reliance but also serves as a practical example of integrating Islamic values with modern economic management. The results of this study indicate that protective economic empowerment can serve as a strategic model for pesantren-based economic development in Indonesia. Furthermore, this model may provide a valuable reference for building a sustainable, independent, and Islamic value-oriented economic system.